A Theory of Ethical Accounting and Its Implications for Hypocrisy in Organizations - Kim, Peter H.; Wiltermuth, Scott S.; Newman, David T. (Academy of Management Review, 2021)
Management scholars have typically regarded the widespread instances of hypocrisy across business, religious, and political institutions to be motivated and strategic. We suggest, however, that hypocrisy may stem not only from people’s motivation to interpret and utilize information in a self-serving manner but also from fundamental differences in people’s access to that information itself. More specifically, we present a multi-stage theory of ethical accounting (TEA) that describes how this differential access to information, specifically about the self versus others, can create an interrelated series of cognitive distortions in how people account for the same unethical behavior. TEA posits that such distortions can allow people to believe they are being fair and consistent when appraising the morality of the self and others while actually being inconsistent in how they do so, and describes how this can ultimately make it harder to address not only hypocrisy but also unethical behavior more broadly in organizations.